Where HTTP fails SOAP alternative choices for situations when HTTP does not scale sufficiently for enterprise Web service deployments. - Lynch, Frank
Web services allow for the delivery of SOAP messages over any protocol. A common misconception is that all SOAP messages must be transmitted over HTTP. While that approach is useful in many cases, there are situations where it makes sense to use alternatives. This paper investigates situations where HTTP does not scale sufficiently for enterprise Web service deployments and looks at available alternatives.